Neisseria meningitidis: Methods and protocols - Hollingshead, S; Tang, C; Deghmane, A; Maiden, M (Humana Press, 2019)
This volume provides methods to analyze the meningococcus and its interactions with biologically relevant host cells and sites, to interrogate the population structure and biology of the meningococcus that defines its capacity to cause disease, and to aid in vaccine development and surveillance. Many of these methods are applicable to the close relative, Neisseria gonorrhoeae, and several of the methods described can also be used in investigating host-pathogen interactions for a range of other organisms. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Neisseria meningitidis: Methods and Protocols will allow for the use of these methods by more laboratories and foster collaboration and consistency in investigations of this enigmatic and dangerous pathogen.